[Eta]-secretase processing of APP inhibits neuronal activity in the hippocampus - Willem, Michael; Tahirovic, Sabina; Busche, Marc Aurel; Ovsepian, Saak V.; Chafai, Magda; Kootar, Scherazad; Hornburg, Daniel; Evans, Lewis D. B.; Moore, Steven; Daria, Anna; Hampel, Heike; Müller, Veronika; et al. (Nature, 2015)
A new pathway for the processing of β-amyloid precursor protein (APP) is described in which η-secretase activity, in part mediated by the MT5-MMP metalloproteinase, cleaves APP, and further processing by ADAM10 and BACE1 generates proteolytic fragments capable of inhibiting long-term potentiation in the hippocampus.
Gesehen am 02.07.2020
Im Titel ist "eta" als griechischer Buchstabe dargestellt